Synchronous acceleration method of the load spectrum for tractor rotary tillage based on wavelet transform - Wang, Yu; Wang, Ling; Wang, Shumao; Zhao, Junsheng (International Journal of Agricultural and Biological Engineering, 2025)
The small load cycle dominates the load spectrum, resulting in inefficient laboratory-based accelerated reliability testing of tractors. While most traditional editing methods focus on accelerating single-type loading spectrum, few are suitable for multi-type loading spectra. This paper proposes a synchronization acceleration method for the rotary tillage load spectrum based on wavelet transform. The method decomposes the power take-off (PTO) torque load data and suspension load data using Daubechies wavelet basis functions, calculates the square sum of cumulative wavelet components at each scale, and identifies large damage segments through threshold setting and Hilbert envelope analysis. Acceleration of the rotary tillage load spectrum is then achieved based on time-domain synchronization. In addition, to measure the acceleration efficiency of load spectrum and find the optimal acceleration parameters suitable for tractor tillage load spectra, a pseudo-damage acceleration efficiency (PDAE) index is proposed to evaluate the acceleration effect. Ultimately, through data comparison, the optimal acceleration parameters suitable for tractor tillage operation load spectra are determined. After acceleration, the time retention ratio of the rotary tillage load spectrum is 85.27%, the damage retention ratio of the PTO torque load spectrum is 97.14%, and the damage retention ratio of the suspension load spectrum is 96.94%. Compared to the damage retention acceleration method, the wavelet acceleration method saves an additional 10.07% of time while maintaining the effectiveness of the load spectrum. This study can provide a reference for accelerating the load spectrum of agricultural machinery and has significant implications for the field of accelerated reliability testing applications. Keywords: tractor, rotary tillage, load spectrum, wavelet transform, load acceleration DOI: 10.25165/j.ijabe.20251801.8468 Citation: Wang Y, Wang L, Wang S M, Zhao J S. Synchronous acceleration method of the load spectrum for tractor rotary tillage based on wavelet transform. Int J Agric & Biol Eng, 2025; 18(1): 124–133.